2(3x+1)+(x-1)=3

Simple and best practice solution for 2(3x+1)+(x-1)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(3x+1)+(x-1)=3 equation:


Simplifying
2(3x + 1) + (x + -1) = 3

Reorder the terms:
2(1 + 3x) + (x + -1) = 3
(1 * 2 + 3x * 2) + (x + -1) = 3
(2 + 6x) + (x + -1) = 3

Reorder the terms:
2 + 6x + (-1 + x) = 3

Remove parenthesis around (-1 + x)
2 + 6x + -1 + x = 3

Reorder the terms:
2 + -1 + 6x + x = 3

Combine like terms: 2 + -1 = 1
1 + 6x + x = 3

Combine like terms: 6x + x = 7x
1 + 7x = 3

Solving
1 + 7x = 3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 7x = 3 + -1

Combine like terms: 1 + -1 = 0
0 + 7x = 3 + -1
7x = 3 + -1

Combine like terms: 3 + -1 = 2
7x = 2

Divide each side by '7'.
x = 0.2857142857

Simplifying
x = 0.2857142857

See similar equations:

| 2(3y-4)=6 | | 3x+3y= | | 5(p-6)=3(p-6) | | (8z+2)(5z+8)= | | 1x+2y=10 | | 5x+4y=26 | | 3x-7=-5y | | 6k-1k=9k-42 | | -83h=1 | | 12=x-6 | | 0.7a+0.3a=2a-4 | | -5-7-3f=-f-2(f+6) | | -w(2w+7)=0 | | .12x+.1=.07x-.15 | | 5-3=0 | | =86.010*LOG(33-15.6)-70.041*LOG(66)+36.76 | | 10x+17=3(3x+8) | | (3x+2)(5-3)=0 | | 5x-8-7x=x+8+x | | 288/5= | | (2-x)(8-4x)= | | 9y+13=6y-2 | | 120+168+-60+-42+-36= | | -10=x+13 | | -2/7= | | 29+104+x=180 | | -2+0+3+-2+-3+1+-4= | | 8(1+5X)+5=13 | | (5x-6)+9=0 | | -(2n-5)=0.5(-12n+30) | | 37+52+x=180 | | 5x-9=6x+17 |

Equations solver categories